Penolakan NYIA dalam Dinding Kota (Analisis Geo-Semiotik pada Jembatan Amarta Yogyakarta) - Bagus Ajy Waskyto Sugiyanto; Latifa Zahra; Fendy Suranto (Jurnal Media dan Komunikasi Indonesia, 2020)
After the construction of the Yogyakarta International Airport (YIA) Airport, various protests emerged. One of the medium used to convey these aspirations is through street art on the walls of the Amarta Bridge. Behind the exposure of the YIA discourse, there are a variety of human activities on the bridge. This study uses geo-semiotic analysis, which is intended to be able to see the space production on the Amarta Bridge. Based on the results of this research, it could be argued that even if the Amarta Bridge has different function, the protests against the YIA through street art in the walls of the Amarta Bridge could be the medium in creating consensus in terms of patterns, attitudes, and support.